Mating behavior in Atheloca subrufella Hulst, 1887 (Lepidoptera: Pyralidae: Phycitinae) - Queiroz, Abel Felipe de Oliveira; Santos, Jakeline Maria dos; Breda, Mariana Oliveira; Santana, Antônio Euzébio Goulart (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2019)
The mating behavior of the moth Atheloca subrufella Hulst, 1887 (Lepidoptera: Pyralidae) was investigated in laboratory arenas. The descriptions of courtship and copulation in males and females were based on direct observations of virgin couples. The courtship and copulation bioassays results comprise several behavior patterns such as antennation, female searching (walking and/or flying); female encounter; female calling behavior; exhibition of pheromone gland; male approach and copulation. For that, courtship and copulation behavior ethograms were presented. The results also suggest that the mating behavior in A. subrufella is mediated by a long-range pheromone and the presence of a short-range pheromone. In overall, this research presents itself as a basis study to further investigations upon A. subrufella sex pheromone and to improve the development of new strategies of behavioral control techniques.